Trunk and lower extremity biomechanics in female athletes with and without a concussion history - Shumski, E. J.; Oh, J.; Schmidt, J. D.; Lynall, R. C. (Journal of Athletic Training, 2024)
Context: Athletes with a history of concussion are at a greater risk for lower extremity musculoskeletal injury. Female athletes may be at an even greater risk than male athletes. Previous researchers on postconcussion landing biomechanics have focused on the lower extremities, but the trunk plays a crucial role as an injury risk factor. Objective: To compare lower extremity and trunk biomechanics during jump-landing and cutting maneuvers between female athletes with and those without a concussion history. Design: Cross-sectional study. Setting: Biomechanics laboratory. Patients or Other Participants: A total of 26 athletes (mean ± SD age = 19.0 ± 1.3 years, height = 1.68 ± 0.07 m, mass = 64.02 ± 6.76 kg, body mass index = 22.58 ± 1.97 kg/m2; median [interquartile range] time since most recent concussion = 37.5 months [25.0 months, 65.8 months]) with a concussion history and 38 athletes (age = 19.0 ± 1.1 years, height = 1.71 ± 0.08 m, mass = 64.72 ± 9.45 kg, body mass index = 22.14 ± 1.80 kg/m2) without a concussion history. Main Outcome Measure(s): Peak kinetics (vertical ground reaction force, vertical loading rate, external knee-abduction moment, and external knee-flexion moment) and kinematics (trunk-flexion angle, trunk lateral-bending angle, ankle-dorsiflexion angle, knee-flexion angle, knee-abduction angle, and hip-flexion angle) were obtained during the eccentric portion of jump-landing and cutting tasks. Separate 2 (group) × 2 (limb) between- and within-factors analyses of covariance were used to compare outcomes between groups. We covaried for time since the most recent concussion and the limb that had a history of musculoskeletal injury. Results: Athletes with a concussion history displayed a greater peak knee-abduction angle in their nondominant limb than their dominant limb (P = .01, np2 =0.107) and the nondominant limb of athletes without a concussion history (P = .02, np2 = 0.083) during jump landing. They also had less trunk lateral bending during cutting compared with athletes without a concussion history (P = .005, np2 = 0.126). Conclusions: Our results indicated landing biomechanics are different between female athletes with and those without a concussion history. This finding may be due to impairments in neuromuscular control postconcussion that may ultimately increase the risk of subsequent lower extremity injury, although further research is warranted given the cross-sectional nature of our study.